Financial Inclusion, Women, and Building Back Better - Hess, Jake; Klapper, Leora; Beegle, Kathleen (World Bank, Washington, DC, 2021)
Financial inclusion occurs when adults have access to appropriate, affordable, and well-regulated financial services to meet their needs effectively and improve their lives. Financial inclusion is a growing global phenomenon. Since 2011, more than one billion adults have opened an account at a financial institution, such as a bank or a mobile money provider. Despite the progress, however, women continue to lag behind men. In low- and middle-income economies, men are 9 percentage points more likely than women to have an account, a gender gap that has stubbornly persisted. And there is considerably variation among countries. Responding to the COVID-19 pandemic, governments across the world are providing relief payments and financial support to citizens and businesses. If such transfers could be transacted digitally, this might help unbanked people, especially women, obtain accounts for the first time. Digital government payments are a proven way to boost women’s financial inclusion. Globally, roughly 140 million people, of which 80 million are women, opened their first accounts to receive digital government payments, such as safety net subsidies, public pension funds, or public sector wage payments, according to the Global Findex (Demirguc-Kunt and others 2018). Government COVID-19 relief and recovery payments create opportunities to rectify the gender gap in financial inclusion, mitigate the pandemic’s economic fallout and build resilience against future emergencies. In addition, the momentum brought on by the policy responses to the pandemic offers opportunities to tackle long-standing challenges to financial inclusion. This note outlines critical priority areas toward this goal.